A Model for Increasing Islamic Financial Inclusion for Coastal Fishing Communities from an Al-Mudharobah Perspective - Mari Patun Hasanah; Muhammad Reza Ardiansyah; Tamamudin; Hendri Hermawan Adinugraha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Financial inclusion is the availability of access to various financial institutions, products and services by the needs and abilities of the community to improve people's welfare. Islamic financial inclusion itself implies the availability of different access to Islamic financial products, services and institutions for the needs of the community. In short, Islamic finance includes how people can access Islamic financial products, services and institutions.  The purpose of this research is an effort to increase the utilization of financial services by coastal communities. This research is a type of qualitative research with a literature study approach. This research uses secondary data. In collecting data, this research uses literature studies such as research journals, scientific articles, research reports, and survey results conducted by government agencies. The result of this research is that coastal fishing communities can implement the development of financial inclusion through an improvement model in sharia financing. The right Islamic financing model for bondet fishermen is mudharabah profit sharing with the implementation of the profit-sharing system carried out by the juragan with fishermen, namely the calculation of the profit sharing system is 2 parts for fishermen and part for the juragan.